2016
DOI: 10.6023/cjoc201511017
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Diazo Compounds Mediated Transition-Metal-Catalyzed C—H Alkylation

Abstract: Diazo compounds had been widely employed as a class of environment friendly and highly efficient coupling reagents in transition-metal-catalyzed C-H bonds insertion reactions. Recently, C-H alkylation of various arenes and heteroarenes has been achieved enormous successes using diazo compounds as the alkylation reagents under a new catalytic model. The recent progress in diazo compounds mediated transition-metal-catalyzed C-H alkylation and tandem C-H alkylation/cyclization is reviewed, including reaction mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
2
8
0
1
Order By: Relevance
“…respectively ( Fig.1 (b) and (c)), consistent with previous observation [13]. Applying TiO 2 overcoating onto the Au/TiO 2 catalyst by ALD at 150 • C would not change the Au particle size, indicated by Fig.1(d) [34]. The insert of Fig.1(d) shows that the thickness of TiO 2 overcoat on 50cTi-Au/TiO 2 was about 1.5 nm, which indicates the growth rate of TiO 2 ALD was about 0.3Å/cycle, consistent with reports in Ref.…”
Section: A Thermal Stability Of Xcti-au/tio2 and Xcal-au/tio2 Catalystssupporting
confidence: 90%
See 3 more Smart Citations
“…respectively ( Fig.1 (b) and (c)), consistent with previous observation [13]. Applying TiO 2 overcoating onto the Au/TiO 2 catalyst by ALD at 150 • C would not change the Au particle size, indicated by Fig.1(d) [34]. The insert of Fig.1(d) shows that the thickness of TiO 2 overcoat on 50cTi-Au/TiO 2 was about 1.5 nm, which indicates the growth rate of TiO 2 ALD was about 0.3Å/cycle, consistent with reports in Ref.…”
Section: A Thermal Stability Of Xcti-au/tio2 and Xcal-au/tio2 Catalystssupporting
confidence: 90%
“…Biener et al demonstrated that an Al 2 O 3 film grown by ALD with even 1 nm thickness can stabilize the nanoporous bulk gold up to 1000 • C, much more sufficient than an 2 nm thick TiO 2 overcoat grown by ALD which can stabilize the nanoporous bulk gold up to 600 • C [33]. We recently demonstrated that TiO 2 ALD overcoat on Au/Al 2 O 3 catalyst significantly improved the CO oxidation activity, where we found that TiO 2 overcoat was preferentially grown at the low-coordination sites of Au nanoparticles [34]. However, applying TiO 2 and Al 2 O 3 ALD overcoat onto supported Au catalysts for improving thermal stability of Au nanoparticles has not been reported.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…磺胺以及 N-取代的衍生物在抗细菌方面有广泛应 用 [279,280] . [285] , 尤其是通过吡唑环构筑的新型抗菌络合物超分 子, 受到特别关注, 成为抗菌药物开发的新方向 [286,287] .…”
Section: 与 Rubr 3 形成的络合物超分子抗菌活性较弱 对大unclassified